2022
DOI: 10.5826/dpc.1204a196
|View full text |Cite
|
Sign up to set email alerts
|

Transepidermal Delivery of Triamcinolone Acetonide or Platelet Rich Plasma using either Fractional Carbon Dioxide Laser or Microneedling in Treatment of Alopecia Areata

Abstract: Introduction: Transepidermal drug delivery,  using “laser-assisted drug delivery'', or microneedling, are new treatment modalities, that can improve drug penetration into skin in treatment of alopecia areata patients. Objective: To evaluate the use of fractional carbon dioxide laser versus microneedling in transepidermal delivery of triamcinolone acetonide and platelet rich plasma in alopecia areata treatment. Methods: Interventional comparative study carried out on 60 patients, randomly divided into four equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Treatment every 2 weeks for 10 total treatments with 12-week follow-up One-half: high pulse energy followed by topical PRP Other half: low pulse energy followed by topical PRP Mean total hair density: increased significantly in high pulse group compared to low pulse group ( p = 0.023) Tolerable pain (7), mild pruritis (2), dandruff (4) Pilot study/0 Hanthavichai et al [ 9 ] AA PRP, TAC (10 mg/mL) AFL (10,600 nm CO 2 ; Advanced Technology Laser Company, Ltd., Shanghai, China) Power: 20 W Density: 4 pulses per inch Pulse duration/time: 3 ms 60 participants randomized with treatment every 3 weeks for four treatments with 4-week follow-up Group 1: laser and TAC Group 2: microneedling and TAC Group 3: laser and PRP Group 4: microneedling with PRP Groups 1 and 3: laser treatment was followed by application of topical drug Groups 2 and 4: drug was applied before, during, and after microneedling Regrowth scales showed microneedling to be more effective than laser for drug delivery ( p = 0.023) with TAC working better than PRP ( p = 0.015). All treatment groups showed improvement Laser: discomfort from heat in some patients Both groups: pain more tolerable than intralesional injections RCT/3 El Mulla et al [ 10 ] AA TAC (20 mg/ml) AFL (CO 2 ), RFMN (both devices not specified) RFMN: Roller: 10-mm-width wheel with 6 coags/disc with 50 pins/coag Depth: 100–150 μm Diameter 80–120 μm Laser: Depth: 150–300 μm Diameter 125–150 μm Case series of 5 patients treated with laser or RFMN then topical TAC then acoustic pressure wave ultrasound (US) All participants had complete resolution of their lesions. Two patients with RFMN after three and six sessions, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment every 2 weeks for 10 total treatments with 12-week follow-up One-half: high pulse energy followed by topical PRP Other half: low pulse energy followed by topical PRP Mean total hair density: increased significantly in high pulse group compared to low pulse group ( p = 0.023) Tolerable pain (7), mild pruritis (2), dandruff (4) Pilot study/0 Hanthavichai et al [ 9 ] AA PRP, TAC (10 mg/mL) AFL (10,600 nm CO 2 ; Advanced Technology Laser Company, Ltd., Shanghai, China) Power: 20 W Density: 4 pulses per inch Pulse duration/time: 3 ms 60 participants randomized with treatment every 3 weeks for four treatments with 4-week follow-up Group 1: laser and TAC Group 2: microneedling and TAC Group 3: laser and PRP Group 4: microneedling with PRP Groups 1 and 3: laser treatment was followed by application of topical drug Groups 2 and 4: drug was applied before, during, and after microneedling Regrowth scales showed microneedling to be more effective than laser for drug delivery ( p = 0.023) with TAC working better than PRP ( p = 0.015). All treatment groups showed improvement Laser: discomfort from heat in some patients Both groups: pain more tolerable than intralesional injections RCT/3 El Mulla et al [ 10 ] AA TAC (20 mg/ml) AFL (CO 2 ), RFMN (both devices not specified) RFMN: Roller: 10-mm-width wheel with 6 coags/disc with 50 pins/coag Depth: 100–150 μm Diameter 80–120 μm Laser: Depth: 150–300 μm Diameter 125–150 μm Case series of 5 patients treated with laser or RFMN then topical TAC then acoustic pressure wave ultrasound (US) All participants had complete resolution of their lesions. Two patients with RFMN after three and six sessions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Each group had treatments every 3 weeks for four treatments. All treatment groups showed improvement; however, regrowth scales showed microneedling to be more effective than laser for drug delivery ( p = 0.023) with TAC working better than PRP ( p = 0.015) [ 10 ]. LEADD with TAC is an effective treatment for AA, but it may not be superior to microneedling-assisted drug delivery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated superior result with combined fractional CO 2 laser and topical drugs in the treatment of different skin diseases such as vitiligo, wart, melasma, and alopecia. [7][8][9][10] In this clinical trial we evaluate the efficacy of the combination of FCO 2 laser and bimatoprost compared to bimatoprost alone in the treatment of alopecia areata.…”
Section: Introductionmentioning
confidence: 99%
“…Transepidermal drug delivery (TDD), in which various ablative techniques create microthermal channels, is a novel noninvasive therapeutic technique to boost the efficacy of topical drugs due to the enhancement of the penetration of topical drug into the dermis and target organ. Previous studies have demonstrated superior result with combined fractional CO 2 laser and topical drugs in the treatment of different skin diseases such as vitiligo, wart, melasma, and alopecia 7–10 . In this clinical trial we evaluate the efficacy of the combination of FCO 2 laser and bimatoprost compared to bimatoprost alone in the treatment of alopecia areata.…”
Section: Introductionmentioning
confidence: 99%